Biochemical parameters and antioxidant property of three salvia l. Taxa endemic in turkey - Emre, İ.; Kursat, M. (Instituto Internacional de Ecologia, 2022)
The aim of the present study was to determine and compare the fatty acids, lipid soluble vitamins, sterols, phenolics, and antioxidant capacities of three endemic Salvia L. taxa (S. euphratica var. Montbret & Aucher ex Bentham leiocalycina (Rech. Fil.) Hedge, S. euphratica var. Montbret & Aucher ex Bentham euphratica (Rech. Fil.) Hedge and S. pseudoeuphratica Rech.Fil.) and to evaluate these results systematically. The fatty acid compositions were determined by using gas chromatography, while the lipid soluble vitamins, sterols, and phenolics were determined by using HPLC. Also, the antioxidant capacities of three Salvia taxa were measured in vitro. Palmitic acid was found as major saturated fatty acid while oleic acid, linoleic acid, ?-linolenic acid, and erucic acid were found as major unsaturated fatty acids in the present study. It was found that S. euphratica var. euphratica had lower palmitic acid (8.94 ± 0.71%), total saturated fatty acid (19.16 ± 0.15%), and higher unsaturated fatty acid content (82.08 ± 0.52%) than other studied taxa. Furthermore, it was shown that S. euphratica var. euphratica had different 18.3/18:2 (0.36) unsaturated/saturated fatty acid (4.28) ratios. However, this study demonstrated that Salvia taxa had low lipid soluble vitamins, sterol contents. On the other hand, it was shown that Salvia taxa had similar catechin (509.2 ± 4.21 µg/g and 552.2 ± 9.21 µg/g) and vanillic acid amounts (351.2 ± 2.17 µg/g and 396.8 ± 4.1 µg/g) in this study. And also, it was found that Salvia taxa had high rosmarinic acid content while S. euphratica var. leiocalycina had the highest rosmarinic acid content (1480 ± 7.57 µg/g). On the other hand, it was shown that the two ferulic acid contents of S. euphratica varieties were higher (1175 ±/5.21 µgmg-1740.2 ± 4.82 µg/mg) than the ferulic acid content of S. pseudoeuphratica of which was the lowest (19.2 ± 0.97 µg/mg). The present results suggested that the biochemical results guided the morphological studies, and Salvia taxa have a potent antioxidant capacity. © 2022, Instituto Internacional de Ecologia. All rights reserved.
Parâmetros bioquímicos e propriedade antioxidante de três espécies de salvia l. Endêmicos da turquia
Keywords: Antioxidant property; Biochemical parameters; GC-MS; HPLC; Lamiaceae